Web Accessibility Web Standards and Regulatory Compliance - Jim Thatcher , Jim Thatcher Michael R. Burks Christian Heilmann Shawn Lawton Henry Andrew Kirkpatrick Patrick H. La (Tucson, 2006)
Itâ€™s easy for a non-disabled person to browse the Web. Point your mouse, see the screen, ignore (or read) the ads and the navigation on a page, and concentrate on the central area of a web page that contains the content. Skim through the headings, search for an interesting picture, and then settle your eye down to read the actual information. Fine and dandy, if you arenâ€™t old and donâ€™t have arthritis, Parkinsonâ€™s disease, or multiple sclerosis, and therefore have the motor control necessary to point your mouse. Itâ€™s a piece of cake to listen to that news report if you arenâ€™t deaf, and easy as pie to find the main content if your vision is good enough to readâ€”or if you are sighted at all. No problem ignoring all those flashing ads, if you donâ€™t have an attention deficit disorder, and no danger of a seizure, if you donâ€™t have photosensitive epilepsy. But what about those people with disabilities? How can they ever hope to use the Web, which was designed for people who can see and use a mouse? The answer is in this book. First, the Web was explicitly designed to be usable without a mouse, and without eyes if necessary. A good deal of what drives the Web and makes it so popular is animation, color, and images. But behind the scenes, underneath the hood of any website (choose your metaphor), lurks the computer code that powers it all. Because the Web was designed to be available to people with disabilities, carefully crafting that code (the â€œmarkupâ€) can make your site much more accessible to people with disabilities. Without damaging the attractiveness of your site to your non-disabled visitors, you can allow users with disabilities to reach, perceive, operate, and understand your content. Therefore, more people will have the opportunity to experience your brand, buy your products, or participate in whatever activity you hope to stimulate with your web presence.